Inter-operator Reliability for Measuring Pulse Wave Velocity and Augmentation Index - Elliot, Catherine A.; Hamlin, Michael J.; Lizamore, Catherine A. (Frontiers in Cardiovascular Medicine, 2020)
Background: Arterial stiffness is a reversible precursor to hypertension. However, research is needed to determine the minimum amount of training required before acceptable arterial stiffness measurements are collected by novice operators. Objective: to compare novice vs experienced operator measurements over a two-week training period to assess when expert-like measures are achieved by the novice operator. Method: Forty-one participants (18 males, 23 females, age: 46.6 ± 14.9 years; BMI: 25.2 ± 3.8; systolic blood pressure: 122.8 ± 14.7 mmHg) received alternating novice and experienced operator arterial stiffness assessments. Measurements included: pulse wave velocity (PWV; using the automatic-capture time-periods of 5- 10- and 20 s) and augmentation index (AIx75) measurements using the SphygmoCor XCEL System v1 (AtCor Medical Pty Ltd., Sydney, Australia). Data were chronologically arranged into quintiles. Results: The intraclass correlation coefficient for PWV substantially improved from quintile 1 (r < 0.8) to quintile 2 and beyond (typically r > 0.8) while AIx75 improved consistently (r = 0.7 in quintile 1 and r = 0.97 in quintile 5). The coefficient of variation was lowest in quintile 4 (PWV: 4.7 – 6% across the 3 measurement time-periods; and 15% for AIx75) but increased in quintile 5 (PWV: 6.2 – 10.5%; and 25% for AIx75). All measurements demonstrated acceptable to excellent reliability after quintile 2. Conclusion: To achieve expert-like PWV measurements in this study, the novice operator underwent a familiarisation session including guided practice measurements on 5 different people, for 10 – 15 minutes per person on two occasions (~2.5 hours). The novice operator then required ≥ 14 practice measurements, with accuracy continuing to improve up to 30 participants. At least 30 training measurements are recommended for novices to take acceptable AIx75 measurements after a familiarisation training.